Implementation of Career Guidance Service Program Evaluation in Senior High Schools - Yulia Anjarwati Purbasari; Nono Hery Yoenanto; Muhari Muhari (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
This study aims to determine the implementation of career guidance services in high school using the Stufflebeam evaluation model, namely Context, Input, Process, and Product (CIPP). This evaluative study used a qualitative descriptive method with data sources, namely the principal, deputy principal, coordinator counselor, counselor,,,class teacher, subject teachers, and students. Data collection in this evaluation monitoring consisted of: (1) open and in-depth interviews; (2) direct observation / observation; and (2) written documents. Data collection was carried out in September - December 2020. The results showed that the evaluation of the Context, Input, Process, Product components in the implementation of career guidance services in SMA was in accordance with the indicators given. Evaluation results are also very important because they can be used to make analysis and follow up in maximizing the career guidance service program. In addition, guidance and counseling teachers can also be accountable for their duties to interested parties such as school principals, supervisors, parents, and other stakeholders. From the results of this study It is hoped that it can provide input and suggestions for BK teachers to continue to carry out evaluations on an ongoing basis.